Improvement of Mathematical Communication Skills of Grade V Elementary School Students Using the Application of the Round-Robin Brainstorming Model - Triwahyuningtyas, Dyah; Azizah, Jamilatul Nur; Sesanti, Nyamik Rahayu (Lentera : Jurnal Kajian Bidang Pendidikan dan Pembelajaran, 2025)
The low mathematical communication skills of grade V students of Kluwut 02 Public Elementary School Malang is the background of this study. In fact, mathematical communication skills are an important component in helping students understand mathematical concepts meaningfully. This research aims to improve students' mathematical communication skills through the application of the round-robin brainstorming learning model. The method used is Class Action Research, which is carried out in two cycles, each consisting of the stages of planning, implementation of actions, observation, and reflection. The research subjects were 16 elementary school grade V students. The data collection technique uses observation and tests in the form of story questions in the Student Worksheet, which are done in groups. The data was analyzed descriptively to determine the improvement of students' mathematical communication skills. The results of the study showed an increase in the percentage of completeness from cycle I by 56.25% to cycle II to 87.5% with the category of good to good. This study fills the gap in the study of the application of round-robin brainstorming at the elementary school level, especially in the development of mathematical communication skills. Although the results showed significant improvement, the study was limited to a small class scope and limited time duration, so further research with a wider scope is needed.